Selection of resistant rootstocks to Meloidogyne enterolobii and M. incognita for okra (Abelmoschus esculentus L. Moench) - Marin, Marcus Vinicius [UNESP]; Santos, Lucas S. [UNESP]; Gaion, Lucas A. [UNESP]; Rabelo, Hudson O. [UNESP]; Franco, Carolina A. [UNESP]; Diniz, Guilherme M. M. [UNESP]; Silva, Edgard H. C. [UNESP]; Braz, Leila T. [UNESP] (Inst Investigaciones Agropecuarias, 2017)
The okra (Abelmoschus esculentus L. Moench) is one of the most important vegetables in the world and is a popular food item in many tropical and subtropical countries. Besides its cultivation for fresh consumption, okra also has potential industrial uses. Nonetheless, pests and diseases remain the most damaging factors affecting its crop yield. Among these, root-knot nematodes are the main pests limiting okra production. This study aimed to determine the responses of plant species of the Malvaceae family to Meloidogyne incognita and M. enterolobii root-knot nematodes, and to also assess the compatibility of the same with the okra commercial 'Colhe Bem IAC'. Resistance was evaluated using the reproduction factor in two commercial okra cultivars (Colhe Bem IAC' and 'Santa Cruz 47'), five cotton (Gossypium hirsutum L.) plant genotypes (PRO 277, IAC 29-233, PR 136, IAC 24, and IAC 03-979), and vinagreira (Hibiscus sabdariffa L.) Other resistance-related traits measured were the percentage of healing, plant height, root length, rootstock stem diameter, scion stem diameter, number of leaves, total fresh weight, and fresh weight of the scion, rootstock, and root parts. While the cotton and vinagreira genotypes tested were resistant to both species of nematodes, okra cultivars were not. The okra, however, showed successful adaptation to grafting, which may offer an important physical resistance against attacks by root-knot nematodes, while vinagreira showed the greatest potential for use as rootstock for protecting okra crops.
Keywords: Gossypium hirsutum; grafting; nematode; plant parasites; root-knot; scion